Pharmacological characterization of high‐affinity σ1 receptor ligands with spirocyclic thienopyran and thienofuran scaffold. (19th November 2019) - Schepmann, Dirk; Neue, Christina; Westphälinger, Stefanie; Müller, Christoph; Bracher, Franz; Lange, Carsten; Bednarski, Patrick; Almansa, Carmen; Friedland, Kristina; Räbiger, Vivien; Düfer, Martina; Wünsch, Bernhard
Abstract: Objectives: In this study, the pharmacological properties of six spirocyclic piperidines 1 –6 showing very high σ1 receptor affinity ( K i = 0.2–16 nm ) were investigated. Methods: In vitro receptor binding studies, retinal ganglion assay and in vivo capsaicin assay were used to determine the affinity, selectivity and activity. Influence on human tumour cell growth (cell lines A427, LCLC‐103H, 5637 and DAN‐G) was determined in different assays. The effect on the ergosterol and cholesterol biosynthesis was determined by GLC/MS analysis. Key findings: Receptor binding studies demonstrated high selectivity for the σ1 receptor. The increased Ca 2+ influx mediated by 2 and the analgesic activity of 1, 4, 5 and 6 confirm σ1 receptor antagonistic activity. Inhibition of human tumour cell growth further supports the σ1 antagonistic effects. Treatment of A427 tumour cells with 2 led to cell detachment and cell degradation. Whereas the ergosterol biosynthesis was not affected, the sterol C14‐reductase, a key enzyme in the cholesterol biosynthesis, was weakly inhibited. Conclusions: Due to the high selectivity, off‐target effects are not expected. The antiallodynic activity underlines the clinical potential of the spirocyclic piperidines for the treatment of neuropathic pain. Due to the antiproliferative activity, the spirocyclic σ1 antagonists represent promising antitumour agents.